RELIGIOUS REFERENCE FOR ARTISTIC CREATIVITY IN THE CIVILIZATIONS OF THE ANCIENT EAST (THE CIVILIZATION OF MESOPOTAMIA AS A MODEL) - Mohamed El Abed Hachelouf (International Journal of Innovative Technologies in Social Science, 2025)
This research paper aims to highlight the presence of both "religion" and "art" in shaping the general civilizational framework of Mesopotamia and to explore the nature of the relationship between them through the material legacy left to us by the Mesopotamian civilization in these two vast knowledge fields. "Religion," in all its aspects and components, occupied a prominent place in the lives of the peoples of Mesopotamian civilization, as it provided solutions to many of the problems threatening the existence and security of the human beings in this civilization. Thinkers of this civilization turned to religion to ensure security in all its forms in various areas of life. These religious beliefs were physically manifested in artistic forms, making "religion" a fundamental reference in shaping artistic work.